Producing ‘internal suspect bodies’: divisive effects of UK counter‐terrorism measures on Muslim communities in Leeds and Bradford - Abbas, Madeline-Sophie (The British journal of sociology, 2019)
Research on UK government counter‐terrorism measures has claimed that Muslims are treated as a ‘suspect community’. However, there is limited research exploring the divisive effects that membership of a ‘suspect community’ has on relations within Muslim communities. Drawing from interviews with British Muslims living in Leeds or Bradford, I address this gap by explicating how co‐option of Muslim community members to counter extremism fractures relations within Muslim communities. I reveal how community members internalize fears of state targeting which precipitates internal disciplinary measures. I contribute the category of ‘internal suspect body’ which is materialized through two intersecting conditions within preventative counter‐terrorism: the suspected extremist for Muslims to look out for and suspected informer who might report fellow Muslims. I argue that the suspect community operates through a network of relations by which terrors of counter‐terrorism are reproduced within Muslim communities with divisive effects.